Withdrawal Notice (American Journal of Biology and Natural Sciences, 2025)
Withdrawal Statement The Editorial Board of the American Journal of Biology and Natural Sciences here by officially announces that the above article has been withdrawn from our publication records. This withdrawal has been made at the request of the author(s) due to a conflict with their affiliated university. The Editorial Board respects the authors’ decision and acknowledges their explanation for this withdrawal. We apologize to our readers for any inconvenience this may cause. The journal remains fully committed to upholding ethical publishing standards in accordance with the COPE (Committee on Publication Ethics) guidelines.